Petrological and geochemical insights into the magma plumbing system of the Daliuchong dacite eruption, Tengchong Volcanic Field, SW China - Su, Chaoxing; Wang, Meng; Luo, Diao; Hou, Tong (Frontiers in Earth Science, 2024)
The formation of highly evolved, dacitic magmas has been attributed to various processes, including crystal fractionation, partial melting of overlying crust, and/or assimilation of crustal material into an evolving magma chamber. These processes are undoubtedly primary processes involved in the formation of dacites, but they may not be the only mechanism involved in the formation of high-silica dacites. For instance, mafic magma replenishment has been proposed as an additional mechanism but has not been assessed, and thus, its role has not been well-constrained. The Daliuchong volcano is the result of one of the largest eruptive events within the Tengchong Volcanic Field (TVF) in southwest China during the Early-Middle Pleistocene. Here, we conducted detailed mineral textures, mineral chemistry, and geochemical studies on Daliuchong pyroclastic rocks to explore the pre-eruptive storage conditions and evolution processes of the magma. The Daliuchong pyroclastic rocks are dacitic in composition. The samples show porphyritic textures characterized by phenocrysts of plagioclase, amphibole, clinopyroxene, orthopyroxene, and Fe-Ti oxides. Additionally, two distinct types of glomerocryst are identified: a gabbroic glomerocryst containing plagioclase + clinopyroxene + orthopyroxene ± Fe-Ti oxides assemblage and a dioritic glomerocryst containing plagioclase + amphibole ± pyroxene ± Fe-Ti oxides assemblage. Both phenocryst and glomerocryst show rich micro-textures. The Daliuchong dacite exhibits bulk compositional heterogeneity. Analysis of bulk-rock data suggests that this heterogeneity may arise from both the differentiation of the dacite itself and the injection of mafic magma. The compositional similarity between the Daliuchong dacite and experimentally produced partial melts of metamorphic basalt supports that the Daliuchong dacite was predominantly formed through the partial melting of the mafic lower crust. Thermobarometry estimation indicates that clinopyroxenes with high Mg# crystallized at 560–870 MPa, whereas amphibole and clinopyroxenes with low Mg# crystallized at 185–300 MPa. Based on the observed phase relations and the calculated crystallization conditions, we propose that during the differentiation of the Daliuchong dacite, heterogeneous dacitic magma formed by partial melting accumulated in a deep magma reservoir (21–32 km) before subsequently ascending toward shallower depths. Crystallization of plagioclase, amphibole, Fe-Ti oxides, and small amounts of pyroxene and apatite occurred at a shallower depth (7–10 km). The presence of coarse-sieve texture, fine-sieve texture, and oscillatory zoning with high amplitude in plagioclase suggests intermittent injection of mafic magma into the shallow magma reservoir, with the eruption of dacitic magma occurring after the final mafic magma replenishment. The petrological evidence above advocates that primitive magma replenishment could have been involved in the formation and triggered the eruption of dacite in the Daliuchong volcano.